POTENSI TEKNIS PEMANFAATAN PELEPAH NIPAH DAN CAMPURANNYA DENGAN SABUT KELAPA UNTUK PEMBUATAN PAPAN SERAT BERKERAPATAN SEDANG - Han Roliadi; Dian Anggraini Indrawan; Gustan Pari; Rossi Margareth Tampubolon (BRIN Publishing, 2012)
Indonesia's tropical natural forest woods are conventionally still raw materials for MDF, which in potency becomes depleted and scarce. Consequently, use of alternative fibrous materials deserves thorough consideration, with their potencies abundant and mostly still unutilized, such as Nypa frutican midrib and coconut coir. In relevant, an experiment was conducted to utilize both kinds of fiber for MDE Those fiber stuffs were each passed through the preparation, and examination of their basic properties (i.e. specific gravity, chemical composition, and fiber dimensions and their derived values). The fibrous pulping for MDF employed a bat semi-chemical soda process under atmospheric pressure, followed with the refining action to achieve pulp freeness at 600-700 mil CSF. The refined pulp were then added with additives (i.z. 4% alum, 3% UF-adbesive, 5% activated charcoal), and then shaped into MDF mat using wet process, followed with beat treatment, bot pressing, conditioning, and ultimately the testing of MDF properties. Scrutiny on MDF physico-strength properties revealed that nypa-midrib fibers were more prospective for MDF than coconut-coir fibers. Activated-charcoal addition lowered the MDF formaldehyde-emission, but decreased its strengths. In properties, MDFs from nyta fibers significantly outperformed those from coconut-cnir fibers in complying with the standard (JIS). Yet, connut-nir fs could still in prospective for MDF by mixing them (pulp form) with nypa-fiber pulp at the proportion (w/w): 25%+75 and 50%+50%